The Political Effects of the 1918 Influenza Pandemic in Weimar Germany - Stefan Bauernschuster; Matthias Blum; Erik Hornung; Christoph Koenig (Center for Economic Studies and ifo Institute (CESifo), 2023)
How do health crises affect election results? We combine a panel of election results from 1893–1933 with spatial heterogeneity in excess mortality due to the 1918 Influenza to assess the pandemic's effect on voting behavior across German constituencies. Applying a dynamic differences-in-differences approach, we find that areas with higher influenza mortality saw a lasting shift towards left-wing parties. We argue that pandemic intensity increased the salience of public health policy, prompting voters to reward parties signaling competence in health issues. Alternative explanations such as pandemic-induced economic hardship, punishment of incumbents for inadequate policy responses, or polarization of the electorate towards more extremist parties are not supported by our findings.
Keywords: D72; I18; N34; H51; 330; pandemics; elections; health; voting behavior; issue salience; issue ownership; Weimar Republic